Analisis Pengaruh Gaya Mengajar dan Kualitas Pembelajaran terhadap Kepuasan Belajar serta Dampaknya pada Motivasi Belajar Mahasiswa di Tangerang Selatan - Zulkifli Zainuddin; Ichsan Gaffar; Sukardi Sukardi; Agung Laksono; Ridho Khansa (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The importance of having enthusiasm and motivation in learning cannot be underestimated. Sometimes we feel down or lose enthusiasm in the learning process. This loss of motivation to learn can occur due to boredom or exhaustion with various daily activities. Even though learning is a child's main task. By studying diligently, students can achieve achievements and become successful children in the future. This research aims to analyze the direct and indirect influence of teaching style, learning quality and learning motivation through learning satisfaction as a mediating variable on students in South Tangerang. This type of research is explanatory with a quantitative approach. This research was carried out by distributing questionnaires to 120 students in the South Tangerang area. The sampling technique used was purposive sampling. The analysis technique used is path analysis and with the help of SPSS version 21 software. This will later determine the direct and indirect influence of each independent variable. From the results of the analysis it was found that the teaching style and learning quality variables had a direct influence on learning motivation. Teaching style and learning quality variables have an indirect influence on learning satisfaction. And the learning motivation variable has a significant direct influence through learning satisfaction.